2021
DOI: 10.1121/10.0003937
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the acoustic field of an ultrasonic pulse induced by a fluidic switch

Abstract: Ultrasonic inspection is a common tool for non-destructive testing in civil engineering (NDT-CE). Currently, transducers are coupled directly to the specimen surface, which makes the inspection time-consuming. Air-coupled ultrasound (ACU) transducers are more time-efficient but need a high pressure amplitude as the impedance mismatch between the air and the concrete is high and large penetration depth is needed for the inspection. Current approaches aim at eliminating the impedance mismatch between the transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…For the piezoelectric transducer the flow outlet plane coincides with the actuation plane. The figure has been adapted from the accompanying study [1] , with the measurement planes being added for this publication. …”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the piezoelectric transducer the flow outlet plane coincides with the actuation plane. The figure has been adapted from the accompanying study [1] , with the measurement planes being added for this publication. …”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The fluidic ultrasonic transducer was connected to a constant source of pressurized air, where a pressure of 1.85 bar was applied to the supply port, 1.2 bar to the passive control port and 1.4 bar to the active control port. Further description of the transducer layout can be found in the accompanying study [1] . A Festo MHJ10 solenoid valve was used to control the active port.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide robust means of testing large concrete structures a fluidic transducer based on a bistable fluidic amplifier was developed. Initial research conducted in [9] have shown that the generation of a broadband ultrasonic signal between 30 kHz and 80 kHz is possible. Fluidic devices also include fluidic oscillators [10,11] that have offered many solutions to modern engineering problems.…”
Section: Introductionmentioning
confidence: 99%